THE EFFECT OF PROJECT BASED LEARNING (PjBL) ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Risa Afianti; Sumarsih Sumarsih; Zainuddin Zainuddin (Universitas Negeri Medan, 2015)
This study aims to find out whether students’ achievement trough using Project Based Learning is higher than trough discussion method in writing procedure text. The research was conducted by experimental research used in two groups. They are experimental use Project Based Learning and control use Discussion Method. The subject of this were the students of SMP Negeri 2 Babalan class VII-2 and VII-3 consisted of 30 students for each class. To collecting the data was taken from writing test. After analyzing the data, it was found that the value of t-obs was 4.16 with degree of freedom (df) = 58 at the level of significance p(0.05) = 2,000. It means that t-obs is higher than t-table. It was found that teaching procedure text by using Project Based Learning is higher than discussion method. Project Based Learning has a significant effect on students’ achievement in writing procedure text. Key words: Project Based Learning, Writing achievement, Procedure Text.